Retinal Findings in COVID-19 Patient: A Literature Review - Tristira Urvina; Erwanda Fredy Purliawan (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Coronavirus disease 2019 (COVID-19) has been declared as worldwide pandemic. The most common symptoms are fever, fatigue, flu-like syndrome and accompanied by respiratory distress. About 10% of patients with COVID-19 in the acute phase show manifestations in the eye, especially in the retina. The activity of the cell surface enzyme protein angiotensin-converting enzyme 2 (ACE2) is believed underlying the clinical manifestations in the eye. This study aim to describe the clinical findings of COVID-19 in the retina which serves as a reference for diagnosis. The study was carried out using the PRISMA method with the keywords "retinal findings in COVID-19", "ophthalmology finding", "retina" and "cotton wool spot COVID-19" with retinal manifestations as an outcome in the literature published in 2020-2021 with search using Google Scholar, SchiHub and Pubmed. There were 14 literatures that matched the inclusion criteria. Involvement of the anterior segment of the eye such as conjunctivitis and keratitis are quite common. The retinal arteries and veins in COVID-19 patients are enlarged due to the inflammatory mediators. The width of the vein diameter is related to the severity of the disease. “COVID-19 retinopathy” has been proposed as a term to describe the appearance of cotton wool spots on the posterior pole of the retina associated with intraretinal hemorrhage without signs of ocular inflammation in COVID-19 patients. With fundoscopic examination, the clinical features of the retina of COVID-19 patients were cotton wool spots, flame shaped hemorrhages or microhemorrhages caused by an inflammatory process in the micro blood vessels in the retina.